Penggunaan Kitab Tashīl al-Masālik ilā Alfiyyah Ibn Mālik dalam Pengajaran Mahārah al-Qirā'ah Santri Tsanawiyah di Pondok Pesantren Besuk - Kholil, Muhammad; Syaifullah, Syaifullah; Syarifuddin, Syarifuddin (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study examines the use of the book Tashīl al-Masālik ilā Alfiyyah Ibn Mālik in developing the reading skills (mahārah al-qirā'ah) of senior-level students at (Pondok Pesantren Besuk). Tashīl al-Masālik is a commentary (syarh) on Alfiyyah Ibn Mālik, a highly influential classical text in the field of Arabic grammar. This qualitative case study aims to explore in-depth how the use of Tashīl al-Masālik can enhance students’ reading comprehension. The research findings reveal that Besuk Islamic Boarding School has integrated Tashīl al-Masālik into its curriculum with a structured and systematic teaching approach. The applied teaching methods include: (1) structured and scheduled learning, (2) the bandongan and question-answer methods, (3) the use of additional learning resources and media, and (4) the sorogan method. Although Tashīl al-Masālik is highly valued in the pesantren tradition for strengthening students’ understanding of Arabic grammar, its integration into the curriculum faces several challenges. One such challenge is the lack of detailed explanations for certain prohibitions, requiring students to consult additional references. Moreover, variations in students’ abilities to comprehend Arabic texts necessitate adjustments in teaching methods.